On the need (and difficulty) of studying the penal state in Costa Rica. Contributions from empirical research - Salazar Araya, Sergio (2022)
The present number arises from the research experiences of, mostly, students who, within the framework of their academic training processes in different disciplinary areas of the UCR. They converge in the identification of both a knowledge gap and a social and institutional urgency to understand and transform the security, justice and punishment system in the country. The contributions mark a milestone in the state of knowledge on the subject, providing an interdisciplinary approach to various aspects of this complex institutional arrangement. The balance is dark and opaque. The former, because the state of the situation reflected in the empirical research and the analysis of the studies exposes a wide and acute crisis. The latter, because to investigate and study this intricate and dynamic system, an institutional dimension of a less and less transparent state, is a methodological challenge that little by little becomes a social and a political one.